Water absorption and acid resistance of oil palm shell lightweight aggregate concrete containing fly ash as partial cement replacement - Nili Wahida, Azhar (2019)
The massive use of aggregates in concrete industry leads to depletion of natural stone such as gravel and granite. The overuse of cement in construction industry causes many environmental problems. In light of environmental impact, the discussion has increasingly focused on using alternative plant-based material and processes such as oil palm shell (OPS) and fly ash (FA) as partial cement replacement. This research is conducted to determine the durability of oil palm shell concrete in terms of porosity, water absorption and acid resistance in concrete containing fly ash. All the specimens were prepared and subjected to curing until 60 days. The condition of curing employed is air curing. The results demonstrate that the concrete with FA have lower compressive strength. The porosity and water absorption of concrete increase when content of FA used is increased. Concrete containing larger amount of FA exhibit higher mass loss and strength deterioration after immersed in sulphuric acid solution. Conclusively, the durability of OPS concrete reduces as larger amount of FA is used.